Recent results and outstanding questions on the response of the electrodynamics of the low latitude ionosphere to solar wind and magnetospheric disturbances - Fejer, Bela G.; Navarro, Luis A.; Chakrabarty, Dibyendu (Frontiers in Astronomy and Space Sciences, 2024)
Storm-time ionospheric electrodynamics effects have been the subject of extensive studies. The solar wind/magnetosphere/ionosphere and thermosphere disturbance wind dynamos have long been identified as the main drivers of low latitude storm-time electrodynamics. Extensive detailed studies showed that climatology of low latitude disturbance electric fields and currents is in good agreement with results from global theoretical and numerical models. Over the last decade, however, numerous studies have highlighted that the response of low latitude electrodynamics to enhanced geomagnetic activity is significantly more complex than previously considered. It is now clear that the electrodynamic disturbance processes are affected by a larger number of solar wind and magnetospheric parameters and that they also have more significant spatial dependence. This is especially pronounced during and after large geomagnetic storms when multiple simultaneous disturbance processes are also active. In this work, we briefly review the main past experimental and modeling studies of low latitude disturbance electric fields, highlight new results, discuss outstanding questions, and present suggestions for future studies.